FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI LQ45 BURSA EFEK INDONESIA - Onny Imanuella Gunawan, 15.05.62.0013; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
This study examines the factors that influence stock prices in companies listed on the Indonesia Stock Exchange LQ45. The sampling method uses purposive sampling. Relationships or influences between variables are explained using multiple linear regression analysis and hypothesis testing (t test). The results show that the Debt to Equity Ratio (DER) variable does not have a significant effect on stock prices, so hypothesis 1 cannot be accepted. Variable Return on Asset (ROA) does not have a significant effect on stock prices, so hypothesis 2 cannot be accepted. Variable Return On Equity (ROE) has a significant effect on stock prices, so hypothesis 3 can be accepted. Net Profit Margin (NPM) variables have a negative and significant effect on stock prices, so hypothesis 4 cannot be accepted. 5). Variable Price to Earning Ratio (PER) does not have a significant effect on stock prices, so hypothesis 5 cannot be accepted. Keywords: DER, ROA, ROE, NPM, PER, and Share Prices